Cover Image. Issue 3 (5th April 2020) - Long, Elliot; Barrett, Michael J.; Peters, Cheryl; Sabato, Stefan; Lockie, Francis
Abstract : The cover image is based on the Original Article Emergency intubation of children outside of the operating room by Elliot Long, Francis D Lockie, Michael Barrett et al., https://doi.org/10.1111/pan.13784 .